Cultivating research skills through scholarly digital storytelling. Issue 7 (10th November 2022) - Schrum, Kelly; Bogdewiecz, Sarah
ABSTRACT: A fundamental responsibility of higher education institutions, across disciplines, is to develop student research skills. The exponential growth of digital scholarship, however, challenges traditional definitions of research. There is a need for deeper understanding of the ways in which students can develop and implement academic research skills and digital research skills simultaneously. This qualitative study explored graduate student engagement in scholarly digital storytelling, a technology-enhanced assessment, across multiple disciplines at a research university in the United States. Findings suggest that students developed the essential research skills of autonomy and flexible thinking along with multimodal research skills throughout the semester-long process of creating scholarly digital stories. Implications for utilizing technology-enhanced assessments, such as scholarly digital storytelling, in higher education are discussed.